Tanggung Jawab Pemerintah Dan Pengusaha Atas Perlindungan Hukum Ketenagakerjaan Terhadap Pekerja Kecelakaan Kerja - Pattipawae, Dezonda R (Faculty of Law, Universitas Pattimura, 2022)
The form of labor protection in Indonesia that must be carried out by every employer or company that employs people to work for the company must be very considered, namely regarding the maintenance and improvement of welfare in the purpose of being held in the form of social security of labor that is general to be implemented or basic, based on joint efforts, family and kegotong royongan as which is listed in the soul and The spirit of Pancasila and the Constitution of the Republic of Indonesia in 1945.The responsibility of employers in the protection of workers is contained in Article 87 paragraph (1) Law No. 13 of 2003 on Employment (State Gazette of the Republic of Indonesia year 2003 Number 39, Supplement to State Gazette of the Republic of Indonesia Number 4279), which affirms that